China’s Mask Diplomacy: Health Assistance for South Pacific Countries During the COVID-19 Pandemic - Amarilys, Monica Rhasintya Indira; Latifah, Emmy (Universitas Sebelas Maret, 2022)
During the COVID-19 pandemic, which generates many negative areas in the field of life, China has become one that shines. China tends to actively contribute to international activities in combating COVID-19. One of the ways is trying to provide assistance to countries affected by COVID-19, one of which is the Pacific countries. This article will explain China's diplomatic efforts to Pacific countries through the distribution of health assistance. Improving China's image is the motive behind this activity. By using the literature study method, this article will discuss more about the reasons behind China's diplomacy in the form of providing health assistance.